TJS 2016
DOI: 10.15547/tjs.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal candidiasis and antifungal assessment of Candida glabrata in patients with HIV infection

Abstract: The purposes of this study were to determine the prevalence of oral mycoflora in HIV + patients and to assay antifungal susceptibility profile of Candida glabrata (C. glabrata) isolates to standard antifungal agents. A total of 100 HIV-infected patients with oropharyngeal candidiasis (OPC) were selected in this study. Susceptibility of C. glabrata isolates to antifungals was determined using the disc diffusion method. A total of 254 yeasts were isolated from the patients. Forty percent (40%) of the patients ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…This difference might be due to the higher prevalence of smoking and alcohol addiction habits among male patients [67, 68]. Among the age groups, the highest prevalence was recorded at the age of 40-49 years (70.4%); this was agreed with Cameron [51] and Iran [52] reports. However, our result disagrees with studies from Brazil [53] and Tanzanian [27] reported the high prevalence of candida species in the age group 30-39 years.…”
Section: Discussionsupporting
confidence: 69%
“…This difference might be due to the higher prevalence of smoking and alcohol addiction habits among male patients [67, 68]. Among the age groups, the highest prevalence was recorded at the age of 40-49 years (70.4%); this was agreed with Cameron [51] and Iran [52] reports. However, our result disagrees with studies from Brazil [53] and Tanzanian [27] reported the high prevalence of candida species in the age group 30-39 years.…”
Section: Discussionsupporting
confidence: 69%
“…Prevalence of these microorganisms in the oral mucosa of patients with HIV/AIDS has been reported elsewhere. ( 18 , 21 , 22 ) C. albicans is the most common species isolated from the oral mucosa of HIV-positive individuals, with prevalence ranging from 70 to 82.1%. ( 23 - 26 ) C. glabrata has emerged as a significant pathogen, particularly in the oral mucosa, either as a co-infecting agent associated with C. albicans or a sole species isolated from oral lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Oropharyngeal infections associated with C. glabrata tend to be more severe and refractory to treatment compared to candidiasis caused by C. albicans alone. ( 17 , 21 , 22 , 27 )…”
Section: Discussionmentioning
confidence: 99%